Modulation of Gut Microbiota, and Morphometry, Blood Profiles and performance of Broiler Chickens Supplemented with Piper aduncum, Morinda citrifolia, and Artocarpus altilis leaves Ethanolic Extracts - Paredes-López, Daniel Marco; Robles-Huaynate, R. A.; Soto-Vásquez, Marilu Roxana; Perales-Camacho, Rosa Amelia; Morales-Cauti, Siever Miguel; Beteta-Blas, Xiomara; Aldava-Pardave, Uriel (Frontiers in Veterinary Science, 2024)
Bioactive plants such as P. aduncum, M. citrifolia, and A. altilis search to improve intestinal health as an alternative to antibiotics as growth promoters (AGP). The objective of this study was to determine the effect of the ethanolic extracts (EE) of these plants on the intestinal health of broiler chickens. Cobb 500 chickens (n=352) were distributed into 8 treatments with 4 replicates and 11 chickens each. T1 received a base diet (BD) and T2 a BD with 0.005% zinc bacitracin. T3, T5, and T7 were supplemented with 0.005% of the diet with EE of these plants while T4, T6, and T8 with 0.01% of the extract. The EEs were supplemented in drinking water, from 1 -26 d. Hematological profiles, blood metabolites profiles; Escherichia coli, Staphylococcus aureus, and Lactobacillus sp. abundance in the ileum mucosa and histomorphometry of the duodenum, jejunum, and ileum mucosa were evaluated. Furthemore, productive performances indices were evaluated. M. citrifolia and A. altilis EE at 0.01% increased blood glucose levels at 21 and 28 days of age respectively and P. aduncum and M. citrifolia EE at 0.01%, increased triglycerides at 28 d of age, in addition this EE did not have any effect on the AST and ALT profiles. The depths of the Lieberkühn crypts, and the villi length to the crypt's depth ratio increased with age on supplementation with 0.01 % M. citrifolia and A. altilis EE at 21 d of age (p<0.05). In addition, the depth of the crypts increased at 28 d of age (p<0.05) in chickens supplemented with 0.01% A. altilis EE. The 0.01% M. citrifolia EE in diet decreased in the Stahylococcus aureus population in the ileal microbiota (p<0.05). The FW, WG during the fattening, and in the three stages overall increased, and the FCR decreased, however, the FI, and the carcasses yield did not change in the broiler chickens supplemented with 0.01% M. citrifolia EE (p<0.05). Conclusively, the M. citrifolia EE at 0.01% of the diet, improved intestinal health and thus the performance indices of the broiler chickens, so it is postulated as a potential alternative to replace AGP in poultry.